A Bibendum-like structure of carbon nitride microtubes with regular arrangement nanotubes for photocatalytic protons reduction. (September 2021) - Huang, Z.; Chen, H.; He, X.; Fang, W.; Du, X.; Li, W.; Zeng, X.; Zhao, L.
Abstract: A novel Bibendum-like structure of g-C3 N4 microtubes (HCN-5) regularly arranged by nanotubes is synthesized for the first time via surfactant induction, and a plausible mechanism for the formation of HCN-5 is proposed. The formation of nanotubes not only provides a convenient way for charge transport but also promotes the enrichment of photogenerated electrons in the active site. The regular arrangement effectively prevents the agglomeration of the nanotubes. These make the photocatalytic water-splitting hydrogen production rate of HCN-5 more than 14 times that of bulk g-C3 N4, reaching 169.6 μmol/h. And, the AQY for H2 evolution reaches 13.1% at 380 nm. The mechanism of improving photocatalytic hydrogen production efficiency and the carrier transfer path is described through DFT calculation. Graphical abstract: A novel Bibendum-like structure of g-C3 N4 microtubes (HCN-5) regularly arranged by nanotubes is synthesized for the first time via surfactant induction, and a plausible mechanism for the formation of HCN-5 is proposed. The formation of nanotubes not only provides a convenient way for charge transport but also promotes the enrichment of photogenerated electrons in the active site. The regular arrangement effectively prevents the agglomeration of the nanotubes. Image 1 Highlights: Surfactant induces the formation of low-dimensional g-C3 N4 . A similar volcanic eruption mechanism that forms tapered microtubules. Nanotubes are regularly arranged to form microtubes. Effectively improve photo-carrier transfer performance.